Comparing the Clinical Utility and Diagnostic Performance of CSF P-Tau181, P-Tau217, and P-Tau231 Assays. (26th October 2021) - Leuzy, Antoine; Janelidze, Shorena; Mattsson-Carlgren, Niklas; Palmqvist, Sebastian; Jacobs, Dirk; Cicognola, Claudia; Stomrud, Erik; Vanmechelen, Eugeen; Dage, Jeffrey L.; Hansson, Oskar
Abstract : Background and Objectives: Phosphorylated tau (p-tau) in CSF is considered an important biomarker in Alzheimer disease (AD) and has been incorporated in recent diagnostic criteria. Several variants exist, including p-tau at threonines 181 (p-tau181), 217 (p-tau217), and 231 (p-tau231). However, no studies have compared their diagnostic performance or association to β-amyloid (Aβ) and tau-PET. Understanding which p-tau variant to use remains an important yet answered question. We aimed to compare the diagnostic accuracy of p-tau181, p-tau217, and p-tau231 in CSF for AD and their association with Aβ and tau-PET. Methods: A total of 629 participants in the Swedish BioFINDER-2 study were included (cognitively unimpaired, n = 334; Aβ-positive mild cognitive impairment, n = 84; AD dementia, n = 119; and non-AD disorders, n = 92). In addition to p-tau181 and p-tau217 measured using assays with the same detector antibodies from Eli Lilly (p-tau181Lilly, p-tau217Lilly ) and p-tau231, we also included p-tau181 measurements from 2 commonly used assays (Innotest and Elecsys). Results: Although all p-tau variants increased across the AD continuum, p-tau217Lilly showed the greatest dynamic range (13-fold increase vs 1.9–5.4-fold increase for other p-tau variants for AD dementia vs non-AD). P-Tau217Lilly showed stronger correlations with Aβ- and tau-PET ( p < 0.0001). P-Tau217Lilly exhibited higher accuracy than other p-tau variants for separating AD dementia from non-AD (area under the curve [AUC], 0.98 vs 0.88 [ p < 0.0001] - 0.96 [ p < 0.05]) and for identifying Aβ-PET (AUC, 0.86 vs 0.74 [ p < 0.0001] and 0.83 [ p < 0.001]) and tau-PET positivity (AUC, 0.94 vs 0.80—0.92, p < 0.0001). Finally, p-Tau181Lilly generally performed better than the other p-tau181 assays (e.g., AD dementia vs non-AD, AUC, 0.96 vs 0.88 [p-tau181Innotest ] and 0.89 [p-tau181Elecsys ]; p < 0.0001). Discussion: CSF p-tau217Lilly seems to be more useful than other included p-tau assays in the workup of AD. Varied results across p-tau181 assays highlights the importance of anti-tau antibodies for biomarker performance. Classification of Evidence: This study provides Class II evidence that p-tau217 provides higher diagnostic accuracy for diagnosis of AD dementia than p-tau181 or p-tau231.